PENGARUH RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP PROFITABILITAS PADA BANK MEGA SYARIAH TAHUN 2015-2023 - Ananda, Gusnita Putri; Rafidah, Rafidah; Kurniyati, Kurniyati (Gapenas Publisher, 2025)
Sharia Bank is a bank that carries out business activities based on sharia principles, or principles of Islamic law regulated in the fatwa of the Indonesian Ulema Council such as the principles of justice and balance ('adl wa tawazun), benefit (maslahah), and does not contain gharar, maysir, usury, unjust and objects that are haram. This research aims to determine the effect of liquidity ratios and solvency ratios on profitability. This research method uses a quantitative method, the sample selection uses a purposive sampling technique which is the determination of the sample and certain criteria, the financial reports studied in 2015-2023 are the financial data of Mega Syariah bank, the data used is secondary data, the data analysis technique uses multiple linear regression. Classic assumption tests, namely (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test). Hypothesis testing (t test and f test) and coefficient of determination (r-square). The results of this research show that partially the liquidity ratio and solvency ratio have a significant effect on profitability. Simultaneously, the liquidity ratio and solvency ratio have a significant effect on profitability.